Analisis Dampak Pemberdayaan Masyarakat Peternak Sapi Perah terhadap Penyerapan Tenaga Kerja Melalui Koperasi Peternak Garut Selatan (KPGS) - Ade Purnawan; Rohimat Nurhasan (Lembaga Layanan Pendidikan Tinggi Wilayah IV, 2019)
This study aims to analyze the impact of community empowerment conducted by Koperasi Peternak Garut Selatan (KPGS) on labor absorption and productivity, especially in cooperative working areas. In this study the authors used descriptive explanatory method with respondents of 94 members of KPGS. The results of data processing shows that the empowerment variable has a positive effect on the variable of labor absorption and productivity variables.